2017
DOI: 10.1186/s13014-017-0801-4
|View full text |Cite
|
Sign up to set email alerts
|

A topology-based method to mitigate the dosimetric uncertainty caused by the positional variation of the boost volume in breast conservative radiotherapy

Abstract: BackgroundTo improve local control rate in patients with breast cancer receiving adjuvant radiotherapy after breast conservative surgery, additional boost dose to the tumor bed could be delivered simultaneously via the simultaneous integrated boost (SIB) modulated technique. However, the position of tumor bed kept changing during the treatment course as the treatment position was aligned to bony anatomy. This study aimed to analyze the positional uncertainties between bony anatomy and tumor bed, and a topology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…The exact recommended placement and number of surgical clips for tumor bed identification with radiation planning varies (2,18,(21)(22)(23)(24)28,29). Clips have been reported to move or 'migrate' from their initial placement location (9,24,25,(30)(31)(32). Clip migration was noted to be similar between groups of patients' XRT 100 days (median 53 days) from surgery to group starting afterward (median 163 days) (31).…”
Section: Surgical Clipsmentioning
confidence: 99%
See 1 more Smart Citation
“…The exact recommended placement and number of surgical clips for tumor bed identification with radiation planning varies (2,18,(21)(22)(23)(24)28,29). Clips have been reported to move or 'migrate' from their initial placement location (9,24,25,(30)(31)(32). Clip migration was noted to be similar between groups of patients' XRT 100 days (median 53 days) from surgery to group starting afterward (median 163 days) (31).…”
Section: Surgical Clipsmentioning
confidence: 99%
“…Clip migration after conventional breast surgery (closing the breast superficially) in comparison to lumpectomy with partial breast reconstruction techniques (sutured cavity) may not differ significantly (31). A potential relationship to body mass index and clip migration may has also been reported (30). Surgical techniques to decrease potential for displacement has been described (16).…”
Section: Surgical Clipsmentioning
confidence: 99%
“…However, the breast position and deformation are susceptible to respiratory motion, setup error and patient immobilization [3,4] . Previous studies have shown that surgical clips implanted in lumpectomy cavity during surgery can improve the accuracy of the target volume delineation and localization [5,6,7,8] . So, for improving the radiation accuracy, surgical clips inserted in are often used to mark the tumor bed.…”
Section: Introductionmentioning
confidence: 99%
“…27 The position of the tumor bed can change in a subset of patients (eg, larger breast volume) during the course of treatment (ie, in distinction to changes in the volume of the cavity discussed above). 28 In 2015, Glide-Hurst et al 29 assessed changes in the lumpectomy cavity during external beam radiation treatment (intrafraction variability) using deformable registration. In this study, 16 left-sided and 1 bilateral breast cancer cases were simulated using both a free-breathing CT as well as a 10-phase 4DCT.…”
mentioning
confidence: 99%
“…Finally, 1 consideration is to record and account for 3D pathologic margins with anisotropic margin expansion of the clinical target volume from the tumor bed to reduce the volume of irradiated volume or to reduce the overall margin due to increased precision of the technology; however, this too can increase the risk of interobserver variation or target misses 27. The position of the tumor bed can change in a subset of patients (eg, larger breast volume) during the course of treatment (ie, in distinction to changes in the volume of the cavity discussed above) 28. In 2015, Glide-Hurst et al29 assessed changes in the lumpectomy cavity during external beam radiation treatment (intrafraction variability) using deformable registration.…”
mentioning
confidence: 99%